Anxiety states in cardiac patients: diagnostics and treatment aspects - G. V. Pogosova (Кардиоваскулярная терапия и профилактика)
The article is devoted to an important issue of anxiety states in general and cardiovascular practice. The author reviews diagnostics of the most prevalent anxiety disorders, as well as relevant modern therapeutic approaches in general practice.